State building in the colonial era : public revenue, expenditure and borrowing patterns in the Cape Colony, 1820-1910 - Gwaindepi, Abel (Stellenbosch : Stellenbosch University, 2018)
Thesis (DCom)--Stellenbosch University, 2018.